Colorant, non-linear optical - Raposo, M. Manuela M. (2014)
Light is composed of an electromagnetic field that can interact with the elementary charges in matter, whose response can in turn influence the behavior of the other light waves. When light passes through any material its electric field induces changes in the polarization of the material´s molecules. In “linear” materials the degree of electron displacement, characterized by the linear polarizability, is proportional to the strength of the applied electric field. The distinguishing characteristic of nonlinear optical colorants is that their polarization response to optical waves depends nonlinearly on the applied electric field strength. This can result in the emission of new radiation fields which are altered in phase, frequency, polarization or amplitude relative to the incident optical radiation. Many of these effects are sensitive to specific characteristics of the local optical properties and interfaces. Multi-photonic absorption can also result in electronic excitations that for a given incident light beam are more strongly localized in space than those resulting from linear absorption processes. Nonlinear optical materials continue to attract the interest of both industrial and academic researchers due to their many versatile applications in the domain of opto-electronics and photonics.